PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN BANTUAN WORDWALL DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA KELAS IV SD - Octaviana, Fadhila; Herpratiwi; Amrina Izzatika; Muhammad Nurwahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this research is that learning in schools is still teacher-centered, resulting in a lack of use of interactive technology-based learning media, which leads to low learning motivation among fourth grade students at SD Negeri 1 Kebon Jeruk. This study aims to determine the effect of implementing the problem based learning model assisted by Wordwall media on the learning motivation of fourth grade students in elementary school. This research uses a quantitative approach with an experimental method, and the design used is a replicated experimental design. The sample in this study consisted of all students from class IVA and IVB at SD Negeri 1 Kebon Jeruk, totaling 51 students. The data collection technique was carried out using a learning motivation questionnaire. The data analysis technique used was the Wilcoxon test. The results of the study show that the implementation of the problem based learning model assisted by Wordwall media has a significant and consistent effect on increasing the learning motivation of fourth grade students at SD Negeri 1 Kebon Jeruk.